Health-information exchange: why are we doing it, and what are we doing? - Kuperman, Gilad J (BMJ Group, 2011)
Health-information exchange, that is, enabling the interoperability of automated health data, can facilitate important improvements in healthcare quality and efficiency. A vision of interoperability and its benefits was articulated more than a decade ago. Since then, important advances toward the goal have been made. The advent of the Health Information Technology for Economic and Clinical Health Act and the meaningful use program is already having a significant impact on the direction that health-information exchange will take. This paper describes how interoperability activities have unfolded over the last decade and explores how recent initiatives are likely to affect the directions and benefits of health-information exchange.